Health Illiteracy among General Populace on Face Mask Use: Vicious Factor during Pandemics - Priya B, Swarna; Begum J, Heeba; Priya M, Yuga; Beevi, Fathima (Journal of Pharmacy Practice and Community Medicine)
Since the global pandemic outbreak has been deteriorating over the current scenario with no definite treatments available the mortality rate has been elevated and the reasons divulge is because of the shorter incubation period resulting in severe atypical pneumonia. This raising disconsolate situation of corona virus and the personal risk of acquiring disease can be altered and prevented by individual protective and preventive measures. Face masks are one of the well-known public interventions as a self-protective measure. The use of face masks among public has become ubiquitous in almost all countries now. But on the same end the measures taken to create awareness about the proper use and disposal of face masks during pandemics are relatively low which can lead to the adverse effects of using preventive equipment’s. In this thrash situation, the present review describes the impact of health literacy among general public on face mask use and disposal, which can tangentially affect the risk of acquiring infection.
Keywords: COVID-19; Pandemic; Preventive precaution use; Mortality rate; Face mask; General public; Health literacy.